Peningkatan Kemampuan Menulis Rangkuman Alur Cerita Fiksi Menggunakan Mind Mapping Dengan Media Canva Pada Siswa Kelas VII A SMP Negeri 1 Jatikalen - Uun Andika Putri; Sri Lestari; Moh. Kasir (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
The purpose of this study was to describe the increase in student achievement in the material of summarizing fictional storylines using mind mapping with Canva media. The subjects of this study were 20 students in class VII A at SMPN 1 Jatikalen. This study used a comparative descriptive approach in which data were collected using test instruments, observation instruments and questionnaire instruments. This research lasted for two cycles. The data presented starts from pre-cycle to cycle II. The results of this study are; 1) Acquisition of increased value is marked by an increase in the highest value from pre-cycle to cycle II. The highest value sequentially in each cycle, namely 8; 85; and 90. 2) There is an increase in learning achievement classically in the learning mastery of students. The percentage increase in learning completeness sequentially in each cycle, namely; 10%, 40%, and 80%. 3) Acquisition of the average value of students also increases in each study. The increase in the average value of students sequentially in each cycle namely 51,25; 66; and 79. Keywords: Summarizing; Mind Mapping; Canva